2018
DOI: 10.1128/aac.02057-17
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Omadacycline in Subjects with Impaired Renal Function

Abstract: Many antibiotics require dose adjustments in patients with renal impairment and/or in those undergoing hemodialysis. Omadacycline, the first aminomethylcycline antibiotic in late-stage clinical development, displays activity against a broad spectrum of bacterial pathogens, including drug-resistant strains. Data from completed phase 3 studies of omadacycline for the treatment of acute bacterial skin and skin structure infections (ABSSSI) and community-acquired bacterial pneumonia (CABP) showed intravenous (i.v.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 14 publications
(16 reference statements)
5
40
0
Order By: Relevance
“…Systemically available omadacycline undergoes negligible biotransformation and is eliminated largely unchanged in feces and urine ( 15 ). Following oral administration, excretion of unabsorbed drug in feces is the predominant route of elimination of omadacycline, with approximately 14% of the total dose and 40% of the absorbed dose being excreted in urine ( 15 , 16 ). The results of this study suggest that hepatic impairment does not have a clinically relevant impact on the PK of omadacycline following oral or i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemically available omadacycline undergoes negligible biotransformation and is eliminated largely unchanged in feces and urine ( 15 ). Following oral administration, excretion of unabsorbed drug in feces is the predominant route of elimination of omadacycline, with approximately 14% of the total dose and 40% of the absorbed dose being excreted in urine ( 15 , 16 ). The results of this study suggest that hepatic impairment does not have a clinically relevant impact on the PK of omadacycline following oral or i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Nonclinical data revealed that omadacycline is cleared hepatically (i.e., by biliary excretion) and renally ( 15 ). Clinical investigations indicate that no adjustment of the omadacycline dose is needed in patients with impaired renal function ( 16 ). The purpose of this study was to determine whether dose adjustment may be necessary for omadacycline in patients with hepatic impairment.…”
Section: Introductionmentioning
confidence: 99%
“…doses ( 16 18 ), and for omadacycline it was approximately 2.6 liters/kg after a single 100-mg i.v. dose ( 19 , 20 ). Thus, these newer compounds exhibit a more extensive tissue distribution than older tetracyclines, as exemplified by tetracycline and doxycycline with volumes of distribution of 1.3 liters/kg and 0.7 liter/kg, respectively ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 A phase I evaluation of 16 subjects, eight with end-stage renal disease (ESRD) and eight healthy, assessed the pharmacokinetics of omadacycline. 20 The AUC values observed were comparable between ESRD and healthy subjects, irrespective of whether the omadacycline dose was administered before or after dialysis. In addition, volume of distribution and overall clearance were comparable between the two groups, suggesting that dosage adjustments are not required for omadacycline in patients with renal dysfunction.…”
Section: Resistancementioning
confidence: 72%
“…A phase I evaluation of 16 subjects, eight with end‐stage renal disease (ESRD) and eight healthy, assessed the pharmacokinetics of omadacycline . The AUC values observed were comparable between ESRD and healthy subjects, irrespective of whether the omadacycline dose was administered before or after dialysis.…”
Section: Pharmacokineticsmentioning
confidence: 99%